Students' Understanding of the Use Of Foreign Terms Contained in the Sports Column of Rakyat Bengkulu Online Newspaper - Genni Genni; Bustomi Bustomi; Randi Randi (Yayasan Karinosseff Muda Indonesia, 2022)
This study aims to determine the ability of Indonesian Language Study Program students at IAIN Bengkulu in understanding foreign terms contained in the sports column of the Rakyat bengkulu online newspaper. Data research methods in quantitative methods are used to describe the data. The results of the research on the use of foreign terms are equally developed due to the influence of globalization and the interaction between one language and another. The difference between loanwords and foreign terms is that loanwords are adapted to Indonesian language rules so that they undergo spelling adjustments according to good and correct Indonesian spelling guidelines, while foreign terms come from books in foreign languages ​​whose use is international and customary by experts in their fields and entered into Indonesian based on: (a) more subtle connotations; (b) short words from the translation; and (c) are international rather than equivalent. It is concluded that the data on the ability to understand foreign terms as language variations in the Rakyat bengkulu online sports column. Based on the calculation, the average value of students' ability to understand foreign terms in the sports column of the Rakyat bengkulu online newspaper is 13.37. Then the percentage obtained is 66.85%. When consulted with a scale of five is quite sufficient. From the discussion above, it can be seen that the average ability of students to understand foreign terms as language variations in the sports column of the Rakyat bengkulu online newspaper is quite adequate with an average value of 13.37. The researcher suggests Indonesian students to understand foreign terms as language variations in the sports column of the Rakyat bengkulu online newspaper. Which has been made with the implementation of learning so that learning takes place in a structured manner.